DESKRIPSI KELAYAKAN BUKU SISWA TEMA 6 KELAS III SEKOLAH DASAR NEGERI 17 PONTIANAK KOTA - Muhamat Alridha Upara; Tahmid Sabri; Dyoty Auliya Vilda Ghasya (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe: (1) the feasibility of contents, (2) the feasibility of the language,(3) the feasibility of the presentation, and (4) the feasibility of graphic in the student booktheme 6 energy and its changes in class III sekolah dasar negeri 17 Pontianak Kota.Thisresearch is a descriptive method that uses a qualititative approach. and the source of thisdata in this study was the homeroom teacher for class III and the student’s book theme 6energy and its changes. Data collection techniques in this study were interviews anddocumentation. Data analysis in this research,data collection,data reduction,datapresentation and verification/conclusion.The results showed that (1) the feasibility of thecontent of the student book theme 6 class III elementary school are on a scale of good tothe percentage of the feasibility of 75%, the deficiency of 25% is on the presentation ofillustrations that are less concrete and the lack of presentation currency of the features thatsupport the material, (2) the feasibility of language books on this theme were on a scalevery well with the percentage of the feasibility of 86% since it is supported by goodlanguage adjustments and the standardization of wording in accordance with correctindonesian language rules, a deficiency of 14% is influenced by linkage and the integrityof the parts, (3) the feasibility of the presentation of the book this theme are on the scalevery well with the percentage of the feasibility of 81%, a deficiency of 19% is influencedby a lack of variation in the presentation, is not presented part glossary, part summariesand concept maps, (4) the feasibility of graphics books on this theme were on a scale verywell with the percentage of the feasibility of 91%, a deficiency of 9% is in the presentationof the contents of the book that reduce the neatness of the utilization of the page and thelack of accuracy as well as concreteness of the illustration.Keywords: feasibility of the content, language feasibility,presentation feasibility, graphicfeasibility